Financial Reporting Gaps and Value Relevance: Chinese Accounting Standards and International Accounting Standards Post-2001 - Dani Foo; Bin Liu; Howard Davey (Asian Academy of Management Journal of Accounting and Finance, 2009)
To gauge the effect of the 2001 official “harmonisation” of the Chinese Accounting Standards (CAS) and International Accounting Standards (IAS) regimes, we examine all companies that simultaneously issued both A and B shares in both the SHSE and SZSE using the Weetman, Jones and Gray (1998) Index of Comparability, testing for differences between companies’ reported earnings and equities. Ohlson’s Value Relevance Model (Ohlson, 1995) is also used, associating stock prices with both earnings and book values of these firms to gauge their relative value relevance. Our findings suggest that reported earnings and equities based on CAS are not significantly different from those based on IAS. We infer from our results that the CAS regime has converged with the IAS more substantially than was previously believed and that most existing literature that involves studying the practical differences of CAS from IAS may have been superseded by these findings. The CAS authorities can be cautiously optimistic about the degree of convergence with IAS.